ONLINE WRITING EXCHANGE WITH OVERSEAS STUDENTS: EFL LEARNERS’ ERRORS AND PERCEPTIONS - Mushoffan Prasetianto; Rizkiana Maharddhika (UIN Alauddin Makassar, 2020)
Writing skill is crucial for non-English students, like agriculture students because students are required to write an abstract of bachelor thesis in English. Nowadays, writing is not only conducted conventionally i.e. using paper and pencil, but also using the internet through online writing exchange. Several studies regarding students’ writing errors have been conducted but error analysis of agriculture students’ writing using online writing is still less researched. To fill this gap, the present study aimed to analyze the types of errors made by agriculture students during joining Online Writing Exchange with Japanese students and students’ perception of the Online Writing Exchange program. 137 students’ writings were analyzed and identified the error and counted the error. Questionnaires and interviews were used to know students’ perceptions. The results showed that there were three types of error made i.e. mechanical, grammatical, and L1-influence error. Students’ perception toward the online writing was positive although they face several difficulties. It is noteworthy that different writing media affect students’ different writing errors.